Defining the structure of undergraduate medical leadership and management teaching and assessment in the UK. (3rd August 2015) - Stringfellow, Thomas D.; Rohrer, Rebecca M.; Loewenthal, Lola; Gorrard-Smith, Connor; Sheriff, Ibrahim H.N.; Armit, Kirsten; Lees, Peter D.; Spurgeon, Peter C.
Abstract: Medical leadership and management (MLM) skills are essential in preventing failings of healthcare; it is unknown how these attitudes can be developed during undergraduate medical education. This paper aims to quantify interest in MLM and recommends preferred methods of teaching and assessment at UK medical schools. Two questionnaires were developed, one sent to all UK medical school faculties, to assess executed and planned curriculum changes, and the other sent to medical students nationally to assess their preferences for teaching and assessment. Forty-eight percent of UK medical schools and 260 individual student responses were recorded. Student responses represented 60% of UK medical schools. 65% of schools valued or highly valued the importance of teaching MLM topics, compared with 93.2% of students. Students' favoured teaching methods were seminars or lectures (89.4%) and audit and quality improvement (QI) projects (77.8%). Medical schools preferred portfolio entries (55%) and presentations (35%) as assessment methods, whilst simulation exercises (76%) and audit reports (61%) were preferred by students. Preferred methods encompass experiential learning or simulation and a greater emphasis should be placed on encouraging student audit and QI projects. The curriculum changes necessary could be achieved via further integration into future editions of Tomorrow's Doctors .